Nesting and Breeding Behaviors of Greater Adjutant Stork (Leptoptilos dubios), a Globally Threatened Stork in District Bhagalpur, Bihar, India - D. N. Choudhary; Abdullah (Emerging Issues in Environment, Geography and Earth Science Vol. 2, 2023)
The goal of the current experiment was to examine the breeding behavior of Greater Adjutant Storks throughout three successive mating seasons from 2019 to 2021 in the flooded areas of the Kosi River in the region of Bhagalpur, Bihar, India. Greater adjutant stork colonies for breeding reached 12 in 2019, 10 in 2020, and 12 in 2021, respectively. 277 chicks were raised in 123 nests in 2019, 282 in 126 nests in 2020, and 236 in 105 nests in 2021, respectively, at these times. The majority of the nest trees were found in and around the settlements, along the sides of the roads. In order to make their nests, storks mostly choose Kadamb, Peepal, Pakar, Gamhar, and Semel trees, with Kadamb being their preferred tree species. The GAS mostly utilized fresh leaves, sticks, and twigs from trees such the Pigeon Wood, Jalebia, Dhaincha, Jamun, Peepal, Gulmohar, Kadamb, and Semal for nesting purposes. Large, spherical nests were formed of plant twigs and were typically found at the tops of trees and at the tips of long, horizontal branches. Both the sexes alternately shared incubation and protection of the chicks after hatching. The breeding season of Greater adjutant stork was recorded between September to April in Bihar. The incubation period was ranging between 37 to 39 days. Two to three chicks on one nest were common. Their successful reproduction is aided by the locals’ tolerance for the birds and the awareness raised for their preservation and conservation by our research team and the local Mandar Nature Club of Bhagalpur. The number of species that are of global conservation concern may increase as a result of farmers’ traditional beliefs paired with straightforward awareness campaigns to maintain community pride.